Evaluating the Molecular—Electronic Structure and the Antiviral Effect of Functionalized Heparin on Graphene Oxide Through Ab Initio Computer Simulations and Molecular Docking - dos Santos, André Flores; Martins, Mirkos Ortiz; Tonel, Mariana Zancan; Fagan, Solange Binotto (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2023: Anais do XVI Simpósio Brasileiro de Bioinformática, 2023)
In antiviral studies, heparin is widely used against the SARS-CoV-2 virus. In this study, computer simulations were performed to understand the role of heparin in a possible blockade of the spike protein binding with the human cell receptor. Another molecule, graphene oxide (GO), was functionalized to interact and bind with heparin to achieve an increase in binding affinity with the spike protein. In the first stage. The electronic and chemical interaction between the molecules were analyzed through ab initio simulations by using Spanish Initiative for SIESTA (Electronic Simulations with Thousands of Atoms) Software. Next, we evaluated the interaction between molecules together and separately in the spike protein target through molecular docking simulations using AutoDock Vina Software. The results were relevant because GO functionalized with heparin exhibited an increase in affinity energy to the spike protein. This affinity indicated a possible increase in antiviral activity. This increase will be verified in the future through in vitro tests. Experimental tests on the synthesis and morphology of the material preliminarily indicate a good interaction between molecules and absorption of heparin by GO. This phenomenon confirmed the results of first principles simulations.